التيارات الفكرية المعاصرة في الجزائر - جباري مسعود (University of Eloued جامعة الوادي, 2024)
الملخص : بعد استقلال الجزائر و استرجاع السيادة الوطنية من فرنسا الاحتلالية الاستيطانية ، ظهرت تيارات فكرية عديدة ، تبنت الإسلام قيما و أحكاما و تعاليم ، فكان منها ما هو مرتبط بالجزائر تنظيميا و ممارسة ، و لم ير مطلقا أن يتدخل آخرون في شأنه الإداري و الهيكلي ، بل عمل على بلورة أفكاره وفق الشأن الجزائري فقط . كما كان هناك تيارات أخرى تأثرت بتوجهات فكرية من عموم العالم الإسلامي ، سواء من مصر أو من الخليج ، بل و حتى من الشرق الإسلامي ، و كان عملها في بيئة جزائرية بكل ما فيها من أعراف و تقاليد وخصوصيات. Abstract After the independence of Algeria and the restoration of national sovereignty from colonialist France, many intellectual currents emerged that adopted Islam’s values, rulings and teachings. Some of them were linked to Algeria in terms of organization and practice. He never saw others interfering in its administrative and structural affairs, but rather worked. To formulate his ideas according to the Algerian issue only. There were also other trends that were influenced by intellectual trends from throughout the Islamic world, whether from Egypt or the Gulf, and even from the Islamic East, and their work was in an Algerian environment with all its customs, traditions, and peculiarities.
Keywords: التيارات الفكرية; البناء الحضاري; الدعوة و التبليغ; السلفية الوهابية; intellectual currents; civilizational construction; invitation and notification; Wahhabi Salafism